Repressor Activity of SqrR, a Master Regulator of Persulfide-Responsive Genes, Is Regulated by Heme Coordination. (10th November 2020) - Shimizu, Takayuki; Hayashi, Yuuki; Arai, Munehito; McGlynn, Shawn E; Masuda, Tatsuru; Masuda, Shinji
Abstract: Reactive sulfur species (RSS) are involved in bioactive regulation via persulfidation of proteins. However, how cells regulate RSS-based signaling and RSS metabolism is poorly understood, despite the importance of universal regulation systems in biology. We previously showed that the persulfide-responsive transcriptional factor SqrR acts as a master regulator of sulfide-dependent photosynthesis in proteobacteria. Here, we demonstrated that SqrR also binds heme at a near one-to-one ratio with a binding constant similar to other heme-binding proteins. Heme does not change the DNA-binding pattern of SqrR to the target gene promoter region; however, DNA-binding affinity of SqrR is reduced by the binding of heme, altering its regulatory activity. Circular dichroism spectroscopy clearly showed secondary structural changes in SqrR by the heme binding. Incremental change in the intracellular heme concentration is associated with small, but significant reduction in the transcriptional repression by SqrR. Overall, these results indicate that SqrR has an ability to bind heme to modulate its DNA-binding activity, which may be important for the precise regulation of RSS metabolism in vivo.